Production of Novel Antimicrobial Peptide Human Beta-defensin 9 (hBD9) Using the Pet Sumo Expression System in Escherichia coli and Characterisation of Its Antimicrobial Activity - Poay Ling Beh; Nurul Atikah Abdul Hamid; Maimunah Abdul Muna’aim; Rukman Awang Hamat; Kok Lian Ho (UPM, 2024)
Indexed by SCOPUS/MYCITE